A Review on Influencing Factors and Suppression Methods of Centrifugal Pump Vibration - Jia Fu Guo; Abdul Mutalib Leman; DongLi Zhang; JinPing Zhang (International Journal of Integrated Engineering, 2026)
As a core auxiliary equipment in power plants, unplanned shutdowns of centrifugal pumps caused by vibration will result in huge economic losses to the plants. This paper aims to systematically elaborate on the generation mechanism, key influencing factors, and suppression methods of flow-induced vibration in centrifugal pumps. Pump body vibration is mainly derived from pressure pulsation generated by internal fluid flow, which acts on the pump body to induce vibration. The main influencing factors include unreasonable setting of pump body geometric parameters, unstable flow conditions, and cavitation. To reduce the intensity of flow-induced vibration, scholars mainly adopt numerical simulation, experimental testing, and a combination of both to formulate optimization strategies, minimizing pressure pulsation inside the pump by optimizing the design of pump body geometric parameters. Research shows that impeller parameter optimization can reduce the amplitude of pressure pulsation, increase pump efficiency by 1.6%~6.71%, and decrease vibration intensity by more than 30%; the multi-volute structure can maximize the reduction of radial thrust by 72% and improve efficiency by 6%~10%; the optimization method combining artificial intelligence/computational intelligence technology with CFD can increase pump operating efficiency by about 27% and shorten model training time by 180s. By sorting out the influence laws of pump body design and operating conditions on vibration, this paper summarizes the mainstream suppression technologies of flow-induced vibration, and clarifies that the application of multi-parameter collaborative optimization, advanced numerical simulation models (DES/LES), and adaptive intelligent algorithms is the key direction to reduce vibration and bridge the gap between theoretical and engineering applications in the future, providing theoretical support and technical reference for the stable operation and optimal design of centrifugal pumps.